Some Results on Warped Product Submanifolds of a Sasakian Manifold - Uddin, S. (Hindawi Publishing Corporation, 2010)
We study warped product Pseudo-slant submanifolds of Sasakian manifolds. We prove a theorem for the existence of warped product submanifolds of a Sasakian manifold in terms of the canonical structure F.